1985
DOI: 10.1093/oxfordjournals.jbchem.a135156
|View full text |Cite
|
Sign up to set email alerts
|

Purification and Some Properties of Phosphoenolpyruvate Carboxylase from Brevibacterium flavum and Its Aspartate-Overproducing Mutant

Abstract: Phosphoenolpyruvate (PEP) carboxylases (PC) were purified from a wild strain and an aspartate-producing mutant of Brevibacterium flavum to electrophoretic homogeneity. The molecular weights of the enzymes were determined to be 4.1 X 10(5) by the gel-filtration technique. Sodium dodecyl sulfate-polyacrylamide gel electrophoresis of the enzyme gave only one protein band with a molecular weight of 1.07 X 10(5). The enzyme was labile and stabilized by substrate PEP, activators, metallic cofactors, an allosteric in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
26
1

Year Published

1987
1987
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(28 citation statements)
references
References 0 publications
1
26
1
Order By: Relevance
“…The enzyme activity of the purified PEPC was assayed by a coupling reaction catalyzed by malate dehydrogenase at 25°C as previously described (15)(16)(17). The standard reaction mixture contained 100 mM Tris-HCl (pH 7.5), 10 mM MnSO 4 , 10 mM NaHCO 3 , 2 mM PEP, 0.1 mM NADH, and 1.5 IU of malate dehydrogenase.…”
Section: Methodsmentioning
confidence: 99%
“…The enzyme activity of the purified PEPC was assayed by a coupling reaction catalyzed by malate dehydrogenase at 25°C as previously described (15)(16)(17). The standard reaction mixture contained 100 mM Tris-HCl (pH 7.5), 10 mM MnSO 4 , 10 mM NaHCO 3 , 2 mM PEP, 0.1 mM NADH, and 1.5 IU of malate dehydrogenase.…”
Section: Methodsmentioning
confidence: 99%
“…A study concerning the enzyme from Brevibacterium ffavum, reported that the mechanism is a rapid equilibrium random Bi Bi with a dead end complex enzyme-bicarbonate-Pi [55]. In view of the large differences in kinetic properties between bacterial and plant PEP carboxylase, a detailed study with the plant enzyme is required.…”
Section: Physiological Rolementioning
confidence: 99%
“…For the amino acid producer Corynebacterium glutamicum, it was originally believed that phosphoenolpyruvate (PEP) carboxylase was the only anaplerotic enzyme for growth on glucose (Ozaki and Shiio, 1969;Mori and Shiio, 1985a); however, later also pyruvate carboxylase activity was demonstrated by Peters-Wendisch et al (1997).…”
Section: Introductionmentioning
confidence: 99%